Lilia Ramos Valverde: her presence in Repertorio Americano - Soto-Ramírez, Marybel (2019)
This essay aims to provide an approach to the writings of Lilia Ramos Valverde that were published in Repertorio Americano by a corpus composed of ten texts that appeared from 1932 to 1950. These texts shed light on the thought of an extraordinary and prolific Costa Rican intellectual woman, whose work has yet to be fully researched